The Effect of Entrepreneurial Orientation on the Employability of Final Year Students - Anissa Lestari Kadiyono; Anselma Ratna Henrieta Sihaloho (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
Unemployment of university graduates has been a severe problem faced by all parties involved in the world of work. Therefore, students are expected to be ready to join the workforce and pursue career development after graduation. This research examined the relationship between entrepreneurial orientation and student employability in facing challenges at the workplace. Entrepreneurial Orientation involves the processes, practices, and decision-making activities aimed at achieving successful outcomes. It impacts students' employability, encompassing the skills, knowledge, and personal attributes that enhance graduates' chances of securing employment and thriving in their chosen careers. This, in turn, benefits the individuals, the workforce, the community, and the economy. This research used a survey method, and the data was collected through an online questionnaire. A total of 478 final-year students of universities in West Java Province, chosen using the quota sampling technique, participated in this study. The linear regression analysis showed a significant influence of entrepreneurial orientation on employability by 50.2%. This shows that entrepreneurial orientation will affect the higher employability of final-year students in their career development.